Researchers’ Presence on Academic Social Networks and Use of Author Identifiers at the University of Puerto Rico, Río Piedras Campus - Penkova, Snejanka (2025)
The study examines the presence and use of Academic Social Networks (ASNs) and author identifiers by faculty at the University of Puerto Rico, Río Piedras Campus. Platforms such as ResearchGate, Academia.edu, Google Scholar, ORCID, and ResearcherID were analyzed, finding limited adoption, with participation levels ranging from 5% to 22%. ResearchGate and Academia.edu are the most widely used platforms, while Web of Science, Google Scholar Citations, and ORCID are used less frequently. Likewise, a lack of standardization in scientific signatures and institutional affiliations was evident, which affects the consistency and visibility of academic production. The results also show that the rank of professor and the Faculty of Natural Sciences account for the majority of activity. Despite institutional efforts to promote the use of ORCID and strengthen digital identity, the impact has been limited. The study concludes that there is a need to implement comprehensive institutional policies and strengthen digital literacy with a view to improving academic identity and the dissemination of research.